2012
DOI: 10.1016/j.regpep.2012.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Tibolone has anti-inflammatory effects in estrogen-deficient female rats on the natriuretic peptide system and TNF-alpha

Abstract: Cardiovascular and immune system abnormalities have been reported in females with estrogen deficiency. To control these disorders in post-menopausal women, hormone replacement therapy (HRT) has been used. Tibolone has been used as a HRT, but the effects of tibolone on the natriuretic peptide system have not been determined. We investigated the effects of tibolone on the natriuretic peptide system and pro-inflammatory cytokines in ovariectomized (OVX) rats. Female rats were divided into four groups: SHAM, OVX, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
1
9
0
2
Order By: Relevance
“…Those treatments lasted 14 days. As previously described [ 35 ], the effects of ovariectomy and estrogen treatment were confirmed by measuring the body and uterine weights at the time of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Those treatments lasted 14 days. As previously described [ 35 ], the effects of ovariectomy and estrogen treatment were confirmed by measuring the body and uterine weights at the time of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, it has been shown that estrogenic compounds regulate oedema, extracellular glutamate levels, reactive astrogliosis and inflammatory response after brain trauma [14, 15]. Therefore, they may be useful molecules for the management of TBI [11]. In the next sections, we review the participation of astrocytes in the response of neural tissue to injury and their role in mediating neuroprotective actions of estrogenic compounds to improve neuronal survival and functional outcomes after TBI.…”
Section: Introductionmentioning
confidence: 99%
“…These effects may be mediated through NPR-A receptors or crosstalk between ERα and NPR-A receptors. 25 , 26 Treatment with ANP alone or with E 2 increased the expression of NPR-A in breast cancer cells and these effects were reduced with antiestrogen in combination with E 2 and ANP. Further studies are warranted to examine the molecular mechanism of NPR-A effects by hormone and antihormone in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%